Complete Long-Term Response to Radioembolization of Hepatic Metastases from Undifferentiated Uterine Sarcoma - Fuad Barakat; Andrea Regine Volker; Dirk Warth; Martin Binnenhei; Peter Reimer; Klaus Tatsch (The Arab Journal of Interventional Radiology, 2023)
We report a case of long-term complete response to selective intra-arterial radiation therapy in a 48-year-old female patient with metastatic liver disease from undifferentiated uterine sarcoma.